The elusive nature of critical codes: - Kramer, Ronald (2016)
This paper engages two ideas put forth by sociologists who are interested in the arts and who have returned to questions of meaning. Amongst such scholars, cultural producers are construed as able to connect with “codes” to create critical works of art. These are then understood to play a pivotal role in redirecting the cultural value systems that constitute our existential frame of reference. Through an interpretive reading of films based on graffiti writing in New York City, I suggest that the relationship between cultural producers and critical codes is fraught with difficulty. Further, when this relationship breaks down we will encounter cultural objects that are more ideological than critical. I conclude by suggesting that culture may not offer a viable space for the pursuit of progressive politics.